Die Arten der afrotropischen Gattung Neoplerochila Duarte Rodrigues, 1982 (Insecta, Heteroptera, Tingidae, Tinginae). - Göllner-Scheiding, Ursula (Contributions to Entomology = Beiträge zur Entomologie, 2007)
The genus Neoplerochila is revised, along with a key for the determination. Eight species of the genus are known now. From these one species is newly described as Neoplerochila millari from the Republic of South Africa and two species of the genus Physatocheila belong now to the genus Neoplerochila. The genus is known only from Namibia and of South Africa. Three of the species are found on Olea spec., the host plants of the other species are unknown. Keywords Heteroptera, Tingidae, Tinginae. Nomenclatural Acts katbergana (Drake, 1953) (Neoplerochila), comb. n. hitherto Physatocheila katbergana millari Göllner-Scheiding, 2007 (Neoplerochila), spec. n. weenenana (Drake, 1953) (Neoplerochila), comb. n. hitherto Physatocheila weenenana